Mechanism of 3D domain swapping in bovine seminal ribonuclease. (13th December 2013) - Spadaccini, Roberta; Ercole, Carmine; Graziano, Giuseppe; Wechselberger, Rainer; Boelens, Rolf; Picone, Delia
<x xml:space="preserve">Abstract</x> 3D domain swapping (3D‐DS) is a complex protein aggregation process for which no unique mechanism exists. We report an analysis of 3D‐DS in bovine seminal ribonuclease, a homodimeric protein whose subunits are linked by two disulfide bridges, based on NMR and biochemical studies. The presence of the covalent bonds between the subunits stabilizes the unswapped dimer, and allows distinct evaluation of the structural and dynamic effects of the swapping with respect to the dimerization process. In comparison with the monomeric subunit, which, in solution has a compact structure without any propensity for local unfolding, both swapped and unswapped dimers show increased flexibility. NMR analysis, together with urea denaturation and hydrogen–deuterium exchange data, indicates that the two dimers have increased conformational fluctuations. Furthermore, we found that the rate‐limiting step of both the swapping and unswapping pathways is the detachment of the N‐terminal helices from the monomers. These results suggest a new general mechanism in which a dimeric intermediate could facilitate 3D‐DS in globular proteins. Structured digital abstract BS-RNase and BS-RNase bind by nuclear magnetic resonance (View interaction)